Psychological Distress Among Older Prisoners: Associations With Health, Health Care Utilization, and the Prison Environment. (October 2016) - Baidawi, Susan; Trotter, Christopher
Physical and functional health issues among older prisoners may be difficult to address in an environment designed for younger inmates. This article investigates the relationships between older prisoners' health, their experiences of the prison environment and health services, and their levels of psychological distress. One hundred and seventy-three older prisoners (aged 50 years and older) from eight Australian prisons were interviewed using the Kessler Psychological Distress Scale, with additional information collected from prisoner interviews and correctional health files. Distress scores were significantly associated with measures of physical health, functional independence, and health care utilization. However, a hierarchical regression analysis determined that physical difficulties in the prison environment and issues accessing prison health care explained a significant proportion of the variation in older prisoners' distress scores.